(untitled) (IPS Journal of Nutrition and Food Science, 2024)
This study investigated the comparative effects of consumption of Garcinia kola and Cola acuminata on some biochemical parameters of Wistar albino rats. Twenty albino rats weighing between 120-180g were divided into four groups. Group A rats fed with normal feed (control), Group B rats fed with 30% of C. acuminata diet, group C rats fed with 30% G. kola diet, group D rats fed with mixture of 15% C. acuminata and 15% G. kola diet. The diet was formulated by mixing homogenously 30% weight by volume (W/V) of G. kola powder and C. acuminata powder with 70% of normal rat feed. The proximate and phytochemical compositions of G. kola and C. acuminata used were evaluated using standard methods. The liver and kidney functions, haematological and lipid profiles were determined using standard biochemical methods. The proximate analysis shows that G. kola has a higher percentage of fat, protein and carbohydrate contents while C. acuminata has a higher percentage of moisture, ash and fibre contents. The result obtained for the phytochemical analysis revealed that G. kola contained a higher percentage of flavonoid, steroid, saponin, anthocyanine, phytate and tannin while C. acuminata has a higher percentage of alkaloids and cardiac glycosides. The results on the kidney function test suggests that G. kola and C. acuminata have no adverse effect on kidney. The results on the Lipid profile showed that daily consumption of G. kola and C. acuminata reduced the serum total cholesterol, the results on the liver function test showed that there was a significant (P<0.05) increase in the AST and ALT levels of group B and D when compared to control. While G. kola has no adverse effect on the liver. The result on haematological analysis showed that group B and D exhibited lower heamatological indices. While group C had no adverse effect on the heamatology. The results shows that, G. kola has more health and medicinal benefits compared to Cola acuminata.